Evaluación y mejoramiento de prácticas agronómicas. Economía - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
Economics research at CIAT in 1985 focused on production studies, marketing studies, and training. Production studies identified farm level constraints, evaluated new technologies as solutions to these constraints, and assessed the adoption of new technologies. Since most beans in Latin America reach the consumer through the market, consumer preferences, market structure, and demand were considered critical factors. Most of the research on these issues was conducted in collaboration with national programs, and strengthening their research capacity through training and joint projects was a major objective. (CIAT)